ESTIMATION DE LA COUVERTURE NEIGEUSE A L’AIDE DE LA TEMPERATURE DE SURFACE DU SOL DANS LE GLACIER ROCHEUX DU COL D’OLEN (ALPES OCCIDENTALES ITALIENNE) : INSTALLATION EXPERIMENTALE ET PREMIERS RESULTATS. - FRATIANNI, SIMONA; COLOMBO, NICOLA; Giaccone, Elisa (Jean-Michel FALLOT, Daniel JOLY, Nadine BERNARD, 2016)
Inference of snow cover duration from ground surface temperatures at the Col d’Olen rock glacier LTER site (NW Italian Alps). Experimental design and first results. In this study the first year results of the surface thermal monitoring at the Col d’Olen rock glacier LTER site (NW Italian Alps) are presented. A total of 74 dataloggers, which measure the Ground Surface Temperature (GST) every three hours, were installed during the summer 2014 in order to study the GST spatial variability and indirectly detect the snow cover duration. Downloaded during August 2015, the temperature data were analysed and the snow cover duration was estimated.